Performance, Correlation and Kinetic Profile of Circulating Serum Fungal Biomarkers of Invasive Aspergillosis in High-Risk Patients with Hematologic Malignancies - Maria Siopi; Stamatis Karakatsanis; Christoforos Roumpakis; Konstantinos Korantanis; Elina Eldeik; Helen Sambatakou; Nikolaos V. Sipsas; Panagiotis Tsirigotis; Maria Pagoni; Joseph Meletiadis (Journal of Fungi, 2021)
As conventional microbiological documentation of invasive aspergillosis (IA) is difficult to obtain, serum fungal biomarkers are important adjunctive diagnostic tools. Positivity rates and the kinetic profiles of galactomannan (GM), 1,3-β-D-glucan (BDG) and Aspergillus DNA (PCR) were studied in high-risk patients with hematologic malignancies. GM, BDG and PCR data from serial serum specimens (n = 240) from 93 adult hematology patients with probable (n = 8), possible (n = 25) and no (n = 60) IA were retrospectively analyzed. Positivity rates and sensitivity/specificity/positive/negative predictive values (NPV) of each fungal biomarker alone and in combination were estimated. The three markers were compared head-to-head and correlated with various biochemical, demographic and patient characteristics. The positivity rates for patients with probable/possible/no IA were 88%/8%/0% for GM (X2 = 55, p < 0.001), 62%/46%/35% for BDG (X2 = 2.5, p = 0.29), 62%/33%/27% for PCR (X2 = 3.9, p = 0.15), 50%/4%/0% for GM + BDG and GM + PCR (X2 = 31, p < 0.001), 50%/8%/22% for BDG + PCR (X2 = 6.5, p = 0.038) and 38%/4%/0% for GM + BDG + PCR (X2 = 21, p < 0.001). Higher agreement (76%) and negative correlation (rs = −0.47, p = 0.0017) was found between GM index and PCR Ct values. The sensitivity and NPV was 45–55% and 90–92% when biomarkers assessed alone and increased to 75–90% and 93–97%, respectively when combined. Weak significant correlations were found between GM, PCR and BDG results with renal/liver function markers (r = 0.11–0.57) with most GM+ and PCR+ samples found in the first and second week of clinical assessment, respectively and BDG later on. Different positivity rates, time profiles and performances were found for the three biomarkers advocating the combination of GM with PCR for the early diagnosis of IA, whereas the high NPV of combined biomarkerscould help excluding IA.